Dutch ministry of LNV further embraces the concept that FLW is significant contributor to GHG emissions and should be addressed from chain perspective - CGIAR Research Program on Climate Change, Agriculture and Food Security (2021)
In several workshop/webinar sessions the findings of our CCAFS research were presented. Consequently, the Dutch Ministry of LNV defined and financed a follow-up project on food-system issues on FLW and relation with climate: "Food Systems Approach: Food Losses & Waste". https://www.wur.nl/nl/onderzoek-resultaten/onderzoeksprojecten-lnv/expertisegebieden/kennisonline/food-systems-approach-food-losses-waste.htm